2014
DOI: 10.11646/phytotaxa.166.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A synopsis of the Asian and Australasian genus Phanera Lour. (Cercideae: Caesalpinioideae: Leguminosae) including 19 new combinations

Abstract: Historically, many authors of regional accounts of the Leguminosae (Fabaceae) tribe Cercideae divided the caesalpinioid genus Bauhinia sens. lat. into several segregate genera including the genus Phanera. However, during the last fifty years, Bauhinia has more often been recognised as a broadly circumscribed taxon with Phanera reduced to a subgenus of Bauhinia sens. lat. The reinstatement of Phanera at generic rank based on molecular and morphological evidence has now been widely accepted, resulting in the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Nevertheless, Phanera is still a somewhat heterogeneous taxon. In particular, as several authors have already noted, the generic boundary of Phanera with regard to Lasiobema warrants more detailed research (Hao et al 2003;Lewis & Forest 2005;Mackinder & Clark 2014;Trethowan et al 2015). Sinou et al (2009) indicated, albeit with weak support, that based on a phylogenetic analysis of nucleotide sequence data from the cpDNA trnL-F region, Asian Phanera are closely related to Lasiobema; although sampling in that study was very limited.…”
Section: Phanera Circumscription and Relationshipsmentioning
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, Phanera is still a somewhat heterogeneous taxon. In particular, as several authors have already noted, the generic boundary of Phanera with regard to Lasiobema warrants more detailed research (Hao et al 2003;Lewis & Forest 2005;Mackinder & Clark 2014;Trethowan et al 2015). Sinou et al (2009) indicated, albeit with weak support, that based on a phylogenetic analysis of nucleotide sequence data from the cpDNA trnL-F region, Asian Phanera are closely related to Lasiobema; although sampling in that study was very limited.…”
Section: Phanera Circumscription and Relationshipsmentioning
confidence: 70%
“…This genus, which is most diverse in Malesia, remains the largest of the segregate genera reinstated from Bauhinia s. lat. (Mackinder & Clark 2014). Nevertheless, Phanera is still a somewhat heterogeneous taxon.…”
Section: Phanera Circumscription and Relationshipsmentioning
confidence: 99%
“…The protologues of all the names have been studied and the current status of the names has been given after scrutiny of relevant literature, viz., de Wit (1956); Thothathri (1965); Larsen and Larsen (1996); Govaerts (1996); Sinou et al (2009) ;Bandyopadhyay et al (2012); Bandyopadhyay (2013a); Mackinder and Clark (2014); Bandyopadhyay (2014) and Bandyopadhyay and Ghoshal (2015).…”
Section: Methodsmentioning
confidence: 99%
“…In five recent publications (Wunderlin 2011, Bandyopadhyay et al 2012, Bandyopadhyay 2013, Mackinder and Clark 2014, Krishnaraj 2014), a total of 73 new combinations have been made in Phanera Lour. occurring in the Palaeotropical region because Bauhinia subgenus Phanera (Lour.)…”
Section: Introductionmentioning
confidence: 99%